Graphene-nanoscroll-based Integrated and self-standing electrode with a sandwich structure for lithium sulfur batteries. Issue 3 (27th November 2019) - Guo, Yi; Zhang, Yin; Sun, Yali; Zhang, Yun; Wu, Hao
Abstract : A sandwich-like and self-standing electrode integrating a current collector, active material and interlayer provides multifunctional polysulfide-trapping ability in lithium sulfur batteries. Abstract : Alleviating the shuttling of polysulfides in a lithium sulfur battery is an important way of improving their electrochemical performance. Herein, sulfur was confined into a graphene nanoscroll (GNS), which was sandwiched by GNS/MnO2 hybrid nanowires to form an integrated electrode. Due to its unique structure and composition, the electrode exhibited a surperior ability to trap polysulfides.